WORD FORMATION IN ENGLISH LANGUAGE - Supervisor: Ruziyeva Umida; Student: Fayzullayeva Dilorom (Modern American Journals, 2025)
This article will walk you through what word formation is, the various types of word formation, examples of each word formation types and the rules to be adhered to when forming words.
Keywords: Formation of the word, prefixes, suffixes, compounding, derivation, borrowing.